(untitled) (International Journal of Engineering and Computer Science, 2017)
Here in this paper we develop a smart Robotic Assistant (RA) that will help human being a lot in multiple ways. The area used is Internet of Things (IoT). The RA can be accessed remotely using human voice commands and gestures. The RA is provided with mechanical arms to pick an object and place it in another location. An Arduino microcontroller based platform is used to develop this smart RA. The RA is controlled with the help of an android platform based IoT device like smart phones etc. The gestures and voice commands are processed using cloud server. The working of RA is as follows the gestures and human voice commands are converted to text form and are then communicated over a Wi-Fi network. The RA is capable of performing different operations like start/stop, move left/right, forward/backward, picking up object and placing it in another location. These peculiarities are really helpful for humans especially for elderly people.